2011
DOI: 10.1089/jcr.2011.0002
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Supplementation Had No Effect on Endurance Capacity in Elderly Subjects Who Had Abstained from Caffeine-Containing Nutrition for 8 Hours

Abstract: Background: In this study, we investigated the effect of acute caffeine ingestion on physical performance after only 8 hours of caffeine abstinence. Methods: The study was a randomized, double-blind, cross-over study and included 30 healthy subject aged ‡ 70 years who had been recruited by their general practitioner. The participants abstained from caffeine for 8 hours (overnight) and the next morning they received placebo and then caffeine (6 mg/kg), or caffeine and then placebo at an interval of 1 week. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…In agreement with the work of Norager et al (15), endurance was also significantly improved (21.4%), however there was no effect of caffeine supplementation on reaction time and cognition. A later study by Jensen et al (17) adds further ambiguity after reporting that a 6mg*kg -1 caffeine supplement did not significantly improve maximal arm flexion strength and isometric submaximal endurance in subjects aged over 70. Furthermore, Jensen et al's study (17) indicated that there was no effect of caffeine on cycling endurance or RPE when compared to placebo.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In agreement with the work of Norager et al (15), endurance was also significantly improved (21.4%), however there was no effect of caffeine supplementation on reaction time and cognition. A later study by Jensen et al (17) adds further ambiguity after reporting that a 6mg*kg -1 caffeine supplement did not significantly improve maximal arm flexion strength and isometric submaximal endurance in subjects aged over 70. Furthermore, Jensen et al's study (17) indicated that there was no effect of caffeine on cycling endurance or RPE when compared to placebo.…”
Section: Introductionmentioning
confidence: 96%
“…A later study by Jensen et al (17) adds further ambiguity after reporting that a 6mg*kg -1 caffeine supplement did not significantly improve maximal arm flexion strength and isometric submaximal endurance in subjects aged over 70. Furthermore, Jensen et al's study (17) indicated that there was no effect of caffeine on cycling endurance or RPE when compared to placebo. The use of RPE in prior studies is also worthy of further consideration.…”
Section: Introductionmentioning
confidence: 96%
“…Whether the effect should be the same following a shorter interval without their usual intake of coffee and tea is not known, and the literature is indeterminate in this respect. [9][10][11][12] Furthermore, we did not distinguish between patients that underwent percutaneous transluminal angioplasty and open surgical reconstruction, even though these groups might have differed in disease severity; we do not know the importance of this. Additionally, the effect of caffeine seemed to be different in different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, both higher and lower doses of caffeine have been shown to be ergogenic in various cognitive and attentional tasks. [3][4][5][6] Comparing any dose-response relationships of caffeine on timing performance would therefore be useful in future research, especially in older adults. Also, the participants in the present study were moderate caffeine users, who abstained from caffeine ingestion for 48 hours prior to engaging in the experimental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Of those that have examined older adults, some have reported no improvements in measures of cognitive or attentional performance. 3,4 Conversely, others have reported improvements in cognitive/attentional performance in older adults following caffeine ingestion. 5,6 These studies 5,6 have subsequently suggested that older adults are more susceptible to the performance-enhancing effects of caffeine than younger adults.…”
Section: Introductionmentioning
confidence: 99%